2000
DOI: 10.1103/physrevlett.84.5808
|View full text |Cite
|
Sign up to set email alerts
|

Resonantly Enhanced Tunneling in a Double Layer Quantum Hall Ferromagnet

Abstract: The tunneling conductance between two parallel 2D electron systems has been measured in a regime of strong interlayer Coulomb correlations. At total Landau level filling n T 1 the tunnel spectrum changes qualitatively when the boundary separating the compressible phase from the ferromagnetic quantized Hall state is crossed. A huge resonant enhancement replaces the strongly suppressed equilibrium tunneling characteristic of weakly coupled layers. The possible relationship of this enhancement to the Goldstone mo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

58
646
0
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 466 publications
(713 citation statements)
references
References 23 publications
58
646
0
1
Order By: Relevance
“…The onset of spontaneous coherence was evidenced by a strong enhancement of the recombination [25] and tunneling [26] rate, respectively. The results of other transport and optical experiments were also consistent with spontaneous coherence of indirect excitons [24,25,[27][28][29][30][31][32][33].…”
Section: Spontaneous Coherence Of Excitonsmentioning
confidence: 99%
See 1 more Smart Citation
“…The onset of spontaneous coherence was evidenced by a strong enhancement of the recombination [25] and tunneling [26] rate, respectively. The results of other transport and optical experiments were also consistent with spontaneous coherence of indirect excitons [24,25,[27][28][29][30][31][32][33].…”
Section: Spontaneous Coherence Of Excitonsmentioning
confidence: 99%
“…This way, one can engineer indirect excitons with radiative lifetimes and spin relaxation times orders of magnitude longer than those of regular excitons [21][22][23]. Due to their long lifetimes, indirect excitons can cool down well below the temperature of quantum degeneracy [24].In earlier studies, evidence for spontaneous coherence was obtained for indirect excitons in coupled quantum wells (CQW) [25] and for indirect excitons in quantum Hall bilayers [26,27]. The onset of spontaneous coherence was evidenced by a strong enhancement of the recombination [25] and tunneling [26] rate, respectively.…”
mentioning
confidence: 99%
“…The incompressible state is represented by the Halperin (111) state, which can also be viewed as a pseudo-spin ferromagnet [76]. This wavefunction encodes the physics of exciton superfluidity, with an associated Goldstone mode [77] and vanishing of Hall resistivity in the "counterflow" measurement setup [78,79]. The existence of an incompressible state (consistent with an exciton superfluid) has been established in numerics [80][81][82][83][84] The case of total filling ν = 2/3, which is the subject of this paper, has been less studied compared to previous examples.…”
Section: Experimental Backgroundmentioning
confidence: 99%
“…However, when d is smaller than a critical distance d c , even in the absence of interlayer tunneling, the system undergoes a quantum phase transition into a novel spontaneous interlayer coherent incompressible phase 2 . At low temperature, with extremely small interlayer tunneling amplitude, Spielman et al discovered a very pronounced narrow zero bias peak in this interlayer coherent incompressible state 4 . M. Kellogg et al also observed quantized Hall drag resistance at h/e 25 .…”
Section: Introductionmentioning
confidence: 99%